Cien por Ciento Cubanos: National Identity, Master Narratives, and Silencing Moves in a Transnational Caribbean Family History. - Findlay, Eileen J. (Latin American Research Review, 2019)
This article focuses on the oral and artifact-filled archive of a working-class Afro-Cuban family to create an intimate set of histories that illuminates the Americas as deeply connected and challenges the limits of national borders. The article explores the ways in which national identities assert themselves in the “private spaces” of migratory life through storytelling and the creation of collective memories, and how gender functions within these spaces. This family has created a master narrative about its own racially conscious, respectable, revolutionary Cuban working-class identity and practice that denies the centrality of international marriage and diasporic experiences to its making. Women’s whispered stories, marginalized from the familial narrative, illuminate alternative meanings and motivations for the strategies that propelled their family into the center of the great conflicts of Cuban history.